PENERAPAN PAKEM KBM DALAM MEWUJUDKAN PENDIDIKAN KARAKTER BANGSA - Hasanah Hasanah (JUPI (Jurnal Pendidikan Indonesia), 2023)
This study aims to describe the improvement in teachers' abilities in managing learning at MIN 3 Mojokerto, after supervision. The method is in the form of real action, namely guiding teachers in carrying out learning activities through academic supervision. The research was conducted in the first semester, precisely in July – November 2022. The subjects of this school action research were class teachers at MIN 3 Mojokerto with a total of 30 teachers. The research results showed that teacher performance increased after taking action in the form of periodic collaborative educational supervision from cycle I to cycle II. These improvements include improvements in preparing learning plans, implementing learning, assessing learning achievement, carrying out follow-up assessments of student learning achievement. For this reason, researchers recommend that educational supervision in schools carry out collaborative educational supervision periodically